Effect of Addition of Melatonin on the Liquid Storage (5°C) of Mithun (Bos frontalis) Semen - P. Perumal; Kezhavituo Vupru; K. Khate (International Journal of Zoology)
The present study was undertaken to assess the effect of melatonin (MT) on sperm motility, viability, total sperm abnormality, acrosomal and plasma membrane integrity, DNA abnormality, antioxidant profiles such as superoxide dismutase (SOD), catalase (CAT), glutathione (GSH) and total antioxidant capacity (TAC), enzymatic profiles such as aspartate amino transaminase (AST), alanine amino transaminase (ALT), and biochemical profiles such as malonaldehyde (MDA) production and cholesterol efflux. Total numbers of 30 ejaculates were collected twice a week from eight mithun bulls and semen was split into five equal aliquots, diluted with the TEYC extender. Group 1 has semen without additives (control) and group 2 to group 5 have semen that was diluted with 1 mM, 2 mM, 3 mM, and 4 mM of melatonin, respectively. These seminal parameters, antioxidant, enzymatic, and biochemical profiles were assessed at 5°C for 0, 6, 12, 24, and 30 h of incubation. Inclusion of melatonin into diluent resulted in significant (P<0.05) decrease in percentages of dead spermatozoa, abnormal spermatozoa, and acrosomal abnormalities at different hours of storage periods as compared with control group. Additionally, melatonin at 3 mM has significant improvement in quality of mithun semen than melatonin at 1 mM, 2 mM or 4 mM stored in in vitro for up to 30 h. It was concluded that the possible protective effects of melatonin on sperm parameters are it prevents MDA production and preserve the antioxidants and intracellular enzymes during preservation.